Oxonantenine Derives from Annona reticulata is a Potential Candidate of DPP-4 Inhibitor for Diabetes Therapy - PRATHITA NITYASEWAKA; DONO INDARTO; YULIANA HERI SUSELO (Nexus Biomedika, 2016)
Introduction: DPP-4 inhibitor is a new diabetic drug for patients with type 2 diabetes who do not achieve normal blood glucose levels using standard drugs such as metformin, sulfonylurea, meglitinide, thiazolidinedione, and ?-glucosidase inhibitor. Pharmacologically, DPP-4 inhibitor increases GLP-1 and GIP blood levels, leading to increase of insulin secretion. So far, Indonesian herbal plants have been used as an alternative therapy for diabetes but their active compounds have been unknown. The aim of this study was to identify phytochemicals derived from Indonesian herbal plants with DPP-4 inhibitor activity. Methods: This study was a bioinformatic study with a molecular docking method. Three-dimensional structure of DPP-4 was downloaded from Protein Data Bank with access code PDB 3F8S. Sitagliptin, a DPP-4 inhibitor, was used as a standard ligand and was obtained from ZINC database with access code ZINC22007143. HerbalDB and Pubchem databases were used to search three-dimensional structures of Indonesian phytochemicals. Before running molecular docking, all phytochemicals were selected using Lipinskis rule of five criteria. Molecular docking of these phytochemicals with DPP-4 was performed three times using Autodock Vina 1.1.2. Results of molecular docking were visualized using PyMol 1.7 and Chimera 1.9. Result: 422 Indonesian phytochemicals were docked with DPP-4. A lower binding affinity was observed in oxonantenine, compared with sitagliptin (-8.3 vs -8.5 kcal/mol respectively). In addition, oxonantenine has as same as binding sites with sitagliptin (Glu 205 and Glu 206). Oxonantenine interacts with DPP-4 at Tyr 547 as third residue, while third residue interaction of sitagliptin and DPP-4 was at Tyr 662. Oxonantenine was found in Annona reticulata. Conclusions: Oxonantenine which is an Indonesian phytochemicals may computationally become a candidate of DPP-4 inhibitor. In vitro study is needed to verify whether or not oxonantenine can inhibit DPP-4. Keywords: DPP-4, type 2 diabetes, molecular docking, oxonantenine.